Mobilitas Sosial Masyarakat Nelayan Di Kecamatan Palabuhanratu Kabupaten Sukabumi - Sheilsa Agvitasari; Reny Sukmawani; Amalia Nur Milla (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
This study aims to deremine the social mobility of fishing communities in Palabuhanratu District, Sukabumi Regency. This research was conducted using a survey method. The result showed that the social mobility of fishing communities in Palabuhanratu District experienced upward social mobility, downward social mobility, and horizontal social mobility seen from changes in employment, wealt, income, and education. As for the data obtained, the fishing community in Palabuhanratu District is dominated by labor fishermen with a total of 83%, and 17% skipper fishermen. Mobility occurs because people want to change their social status for the better. Both in terms of income, wealth and education for their children. With regard to the results of this study, it is important to design various strategies for empowering fishing communities in Palabuhanratu District so that fishing communities can develop towards modern and better ways to increase fish catch production.